Living with Medicines: Drawing Healing Correspondences on the Caribbean Coast of Colombia - Helmesi, Dariel (Université d'Ottawa / University of Ottawa, 2024)
While the use of psychedelics in biomedicine has generated a new momentum, many communities worldwide have always maintained practices and correspondences with powerful master plants (Doyle, 2012; Langlitz, 2013). Often sprouting within "third nature" spaces, ancestral medicine communities and practices offer much broader ways of addressing cosmological, environmental, and medical issues (Tsing, 2015). Amidst global health concerns and ongoing climate crises, ancestral healing practices and medicines provide crucial insights into healing processes with and through the land, with a focus on respect, permission, harmony, and paying the land. Situated on the outskirts of the Caribbean port city of Barranquilla, Colombia, Casa Zindulí emerges as a prosperous yet informal ancestral healing site for friends, families, and inhabitants of Barranquilla to learn and live with the medicines of the Colombian territories. Through a labour of love and patience, Casa Zindulí has established itself as the host of numerous events, ceremonies, and gatherings with trusted Awá, Sikuani, Uitoto and Arhuaco traditional healers and Elders from both Colombia and Ecuador. Drawing from Tim Ingold's "correspondences" (2015; 2021), this thesis attends to the myriad of healing correspondences in a world of becoming, of the in-between, or "the very medium in which our lives are mixed and stirred" (Ingold, 2015, p. 147; 149). Employing a combination of fieldnote drawings, fictional methods and imagination inspired by the graphic ethnography boom in anthropology (Theodossopoulos, 2022) and the imaginative logic of discovery (Taussig, 2011), this thesis adds nuance to the understanding and storytelling of how people and plants come together in healing ways on the Caribbean Coast of Colombia, contributing to the growing discourse on human-environment relations and the potential of ancestral healing practices, and creative methods in anthropology, in addressing contemporary global challenges.
Keywords: ancestral healing; anthropology; plant medicine; ethnography; drawing; fictional methods; ayahuasca; yopo; coca; Colombia